Modelagem de percepção de humanos virtuais baseada em dados geométricos e ray-casting - Pletsch, Eliéser Lourega (Universidade do Vale do Rio do Sinos, 2006)
This work presents a perception data model which deals with not visible information (such as hearing and smelling). This model is based on geometric information that exists in the virtual environment. This proposal also identifies several research topics related to autonomous agents in virtual environments and their perception abilities. Investigations in synthetic vision area allows to find methods that could be generalized in order to be used for other sensors. Therefore, the main objective of this model is to allow to the agents the possibility of identifying different events, into a virtual environment, not necessarily visual data. For instance, the presence of smell and noise. In addition, we propose methods which aims to provide a good computational performance and which can be generalized and implemented in a way that they can provide the perception methods to virtual human beings.
Keywords: agentes autônomos; humanos virtuais; olfato sintético; percepção; visão sintética; autonomous agents; perception; synthetic smell; synthetic vision; virtual human being; Ciências Exatas e da Terra